Concomitant loss of cell surface fibronectin and laminin from transformed rat kidney cells - Hayman, EG (The Rockefeller University Press, 1981)
Both fibronectin and laminin were found by immunofluorescence as a matrix at the surface of normal rat kidney cells. These matrices were absent from the surface of virally transformed rat kidney cells. Soluble fibronectin and laminin were detected in the culture media of the transformed as well as the normal cells. Culture supernates of the transformed cells contained even more fibronectin than the supernates of the transformed cells contained even more fibronectin than the supernates of the normal cells while laminin was present in similar amounts in both culture media. This shows that the loss of fibronectin and laminin from the surface of the transformed cells is caused by failure of the cells to deposit these proteins into an insoluble matrix and not caused by inadequate production. Fibronectins isolated from culture media of the normal and transformed cells were similar in SDS polyacrylamide gel electrophresis. Laminin isolated from culture media by affinity chromatography on heparin-Sepharose followed by immunoprecipitation was composed of three main polypeptides, one with a molecular weight of 400,000 and two with a molecular weight close to 200,000 in both cell types. Fibronectins from both cell types were equally active in promoting cell attachment. Rat fibronectin from transformed cells, like normal cells, when applied to culture dishes coated with fibronectin, readily attached and spread on the substratum, requiring approximately the same amount of fibronectin as the normal cells. On the basis of these results it seem that the failure of the transformed cells to incorporate fibronectin into an insoluble cell surface matix is not a consequence of a demonstrable change in the functional characteristics of the fibronectin molecule or in the ability of the cells to interact with fibronectin. It may depend on as yet unidentified interactions of the cell surface. Similar interactions may be needed for the deposition of laminin into the matrix, because laminin was also absent from the surface of transformed cells, despite its being synthesized by these cells.